Immunomodulatory Effects of Canine Adipose Tissue Mesenchymal Stem Cell-Derived Extracellular Vesicles on Stimulated CD4+ T Cells Isolated from Peripheral Blood Mononuclear Cells - Takahiro Teshima; Yunosuke Yuchi; Ryohei Suzuki; Hirotaka Matsumoto; Hidekazu Koyama (Journal of Immunology Research)
Adipose tissue-derived mesenchymal stem cells (ADSCs) have anti-inflammatory and immunomodulatory characteristics. Many studies have suggested that the immunomodulation of ADSCs is largely mediated by secreted paracrine factors. Various factors are secreted from ADSCs, among which extracellular vesicles are considered to play a major role in the communication between ADSCs and target cells. Several studies have reported the function of canine ADSC-derived extracellular vesicles (cADSC-EVs), but few studies have reported the immunomodulatory effects of cADSC-EVs on immune cells. The purpose of this study was to investigate the effects of cADSC-EVs on in vitro-stimulated CD4+ T cells isolated from peripheral blood mononuclear cells (PBMCs). cADSC-EVs were isolated from cADSCs under naive conditions or primed conditions by tumor necrosis factor-α (TNFα) and interferon-γ (IFNγ). The expression levels of several microRNAs in cADSC-EVs were altered by priming with TNFα and IFNγ. Culturing PBMCs stimulated with concanavalin A in the presence of naive or primed cADSC-EVs inhibited the differentiation of PBMCs and CD4+ T cells and promoted apoptosis of PBMCs. CD4+, CD8+, and CD4+CD8+ T cells were decreased, while CD3+CD4-CD8- T cells were increased. T helper (Th) 1, Th2, Th17, and regulatory T (Treg) cells were analyzed by flow cytometry. cADSC-EVs inhibited the proliferation of Th1 and Th17 cells and enhanced Th2 and Treg cell proliferation. However, CD4+ T cells that had incorporated labeled cADSC-EVs comprised only a few percent of all cells. Therefore, these responses of stimulated CD4+ T cells may be due to not only direct effects of cADSC-EVs but also to indirect effects through interactions between cADSC-EVs and other immune cells. In conclusion, cADSC-EVs exert immunosuppressive effects on stimulated CD4+ T cells in vitro. These findings may be useful for further studies of immune diseases.